Traumatic common carotid artery-internal jugular vein fistula in an acute setting: A case report with review of literature - Ezaz Ahmed; Aamir Mohammad; Saifullah Khalid; Syed Shamayal Rabbani; Mohd Azam Haseen; Areeba Khursheed (Annals of Vascular Surgery - Brief Reports and Innovations)
Introduction: Arteriovenous fistulas may be due to trauma or due to iatrogenic causes. These patients present with non specific symptoms such as high output heart failure years later after the development of the fistula. Formation of the fistula in an acute setting immediately after the trauma is a rare occurrence. Here we present a case of a 19 year old boy who presented with a fistula a few hours after the trauma. Case Summary: A 19 year old boy with history of firearm injury to the left side of the neck presented with a palpable thrill and an audible bruit over the site of injury. CT Angiography was done which showed multiple pseudo aneurysms arising from the left common carotid artery(CCA) and a communication with the adjacent internal jugular vein(IJV). Endovascular embolisation of the fistula was done and a stent was placed across the fistula. On check angiography, no fistulous communication was noted between the left CCA and IJV post procedure and the patient was discharged under stable conditions. Conclusion: Traumatic AVFs involving the common carotid artery and internal jugular veins is not uncommon but usually presents after a period of time with added morbidity, and has been not been reported frequently. Also, the fistulas present much later unlike in this case report which presented very early. Ultrasound or CT angiogram may aid in diagnosis. However, conventional angiogram is the gold standard for diagnosis with interventional techniques available for managing these high flow fistulas with a good technical success and acceptable safety profile.